Insulin resistance contribution to pathogenesis of cardiac remodeling in patients with hypertension in combination with obesity and type 2 diabetes - M. E. Statsenko; M. V. Derevyanchenko (Российский кардиологический журнал, 2020)
Aim. To evaluate the insulin resistance contribution to pathogenesis of left ventricular (LV) remodeling in patients with hypertension (HTN) in combination with obesity and type 2 diabetes (T2D).Material and methods. The study included 320 patients with stage II-III HTN and stages 1-3B chronic kidney disease (CKD) aged 45-70 years: group 1 (n=102) — HTN patients only, group 2 (n=90)  — patients with HTN and obesity, group 3 (n=96) — patients with HTN, obesity and T2D, group 4 (n=32) — patients with HTN and T2D. The groups were comparable in main clinical and demographic parameters. We performed a clinical examination, assessed cardiac structure, insulin levels and insulin resistance indices. We used nonparametric statistics, multiple regression, stepwise linear discriminant and canonical analyzes. Data are presented as Me [Q25; Q75], where Me is the median, Q25 and Q75-25 and 75 percentiles, respectively.Results. LV mass index was significantly higher in the group of HTN, obesity and T2D compared with HTN patients only (107,5 [9,5; 125,6] vs 96,0 [85,1; 106,1] g/m2 , respectively). The percentage of patients with LV hypertrophy was significantly higher in groups 2, 3 and 4 compared with group 1, and also in group 3 compared with groups 2 and 4. A stepwise discriminant analysis revealed that BMI increase in HTN±T2D patients was accompanied by an increase in values of metabolic index, triglyceride-to-highdensity-lipoprotein-cholesterol ratio. Canonical analysis showed that an increase in the median values of Insulin Resistance function in all groups was associated with a deterioration in the median values of Cardio function.Conclusion. The data obtained specifies the LV geometry characteristics, as well as the insulin resistance contribution to pathogenesis of LV remodeling in HTN patients with/without obesity and/or T2D.